2020
DOI: 10.1021/acsomega.0c02629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biomass Carbonization on the Grinding of Coal/Biomass Mixtures

Abstract: To increase the co-firing ratio of biomass in existing pulverized coal-fired power plants, biomass should be pulverized to obtain a particle size suitable for combustion. However, evaluation of the particle size distribution of each coal and biomass mixture via traditional fuel analysis is difficult. Because coal does not contain neutral sugars, the particle size distribution of biomass in the mixture can be estimated based on its neutral sugar content. The current study was conducted to evaluate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…The findings of this study also showed that as the WP mixing ratio increased, the proportion of small particles in the grinding mixture decreased. The respective particle size distributions of coal and WPs in each mixture were estimated based on the neutral sugar content according to the method reported in our previous study, 25 and the results are given in Figure 4. As the WP mixing ratio increased, the ratio of the large biomass particles in the mixture increased.…”
Section: ■ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings of this study also showed that as the WP mixing ratio increased, the proportion of small particles in the grinding mixture decreased. The respective particle size distributions of coal and WPs in each mixture were estimated based on the neutral sugar content according to the method reported in our previous study, 25 and the results are given in Figure 4. As the WP mixing ratio increased, the ratio of the large biomass particles in the mixture increased.…”
Section: ■ Discussionmentioning
confidence: 99%
“…When a coal sample does not contain neutral sugar and only WPs contain neutral sugar, the biomass content in the mixture can be estimated from the following equation: …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations